Recent advances in exosome-based immunotherapy applied to cancer - Xie, Jindong; Zheng, Zihan; Tuo, Ling; Deng, Xinpei; Tang, Hailin; Peng, Cheng; Zou, Yutian (Frontiers in Immunology, 2023)
Cancer stands as a prominent contributor to global mortality rates, necessitating immediate attention towards the exploration of its treatment options. Extracellular vesicles have been investigated as a potential cancer therapy in recent years. Among them, exosomes, as cell-derived nanovesicles with functions such as immunogenicity and molecular transfer, offer new possibilities for immunotherapy of cancer. However, multiple studies have shown that exosomes of different cellular origins have different therapeutic effects. The immunomodulatory effects of exosomes include, but are not limited to, inhibiting or promoting the onset of immune responses, regulating the function of molecular signaling pathways, and serving as carriers of antitumor drugs. Therefore, this mini-review attempts to summarize and evaluate the development of strategies for using exosomes to package exogenous cargos to promote immunotherapy in cancer.